Výroba součásti z plastu - Enekeš, Lukáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2008)
Projekt vypracovaný v rámci bakalárskeho štúdia oboru 2307 predkladá návrh technológie výroby plastovej súčiastky – pätka nohy stola z materiálu polyamid Pa- 6. Na základe literárnej štúdie problematiky výroby technických plastových dielcov technológiou vstrekovaním plastov do formy. Prvá časť bakalárskej práce popisuje rozdelenie a identifikáciu plastov. V ďalšej časti sú určené technologické parametre a navrhnutie výrobného stroja s nástroja vrátane výkresovej dokumentácie. Na záver je prevedená jednoduchá kalkulácia výrobných nákladov.

The project elaborated in frame of engeneering studies branch 2307. The project is submitting a design for production technology for a plastic part- bottom end of table leg made of polyamid Pa- 6. Pursuant to the literary pursuit of the problem production issues on the technical plastic segments by the technology of the injecting of a plastic into the mould (by injection mould technology). In the first part devision and identification of plastic materials are described. In the next part technological parameters and a design of the manufacturing machine and tool, including a drawing documentation, are determined. In the conclusion a simple calculation of the production costs is carried out.
Production single parts from thermoplastic
Keywords: plastová súčiastka; technológie vstrekovania; tvárnenie plastov; vstrekovacia forma; plastic segment; the technology of the injecting plastic forming; plastic forming; the injection mould